A novel modeling of volumetric errors of three-axis machine tools based on Abbe and Bryan principles. (April 2020) - Huang, Y.B.; Fan, K.C.; Lou, Z.F.; Sun, W.
Abstract: The modelling of volumetric errors of machine tools has been widely used by the method of Homogeneous Transformation Matrix (HTM) based on rigid body kinematics analysis for a long time. Without spindle induced errors and thermal errors, to establish a closed-loop HTM for a three-axis machine tool, the total of 21 geometric errors are the primary elements to be known. It is well known that the measured points of translational errors are directly related to the volumetric error at the tool cutting point through rigid body kinematics. In the generalized HTM method, however, this relationship is missing. This report, therefore, proposes a new comprehensive approach to formulate the volumetric errors based on the famous Abbe principle in order to derive the error term in the motion direction, and Bryan principle to derive the error terms in orthogonal to the motion direction. The proposed methodology is simple in concept, rational in physical meaning and easy in implementation. Experimental results, including faster multi-degree-of-freedom error measurements, volumetric error analysis and compensation on a testbed of small machine tool, validate the correctness and effectiveness of this method. Graphical abstract: Image 1 Highlights: This new method is more physically reasonable than the popular Homogeneous Transformation Matrix method. An embedded sensor system for detecting 5-DOF geometric errors of a linear stage has been developed and equipped into an investigated small NC machine tool. Through error measurement and compensation experiments, the correctness and feasibility of this new model have been verified.